Farklı uygulama basamaklarında oluşan tükürük kontaminasyonunun 3 adeziv sistemin dentine bağlanma dayanımlarına etkisinin incelenmesi - Esra Cengiz; Hikmet Solak (Cumhuriyet University, 2014)
Objectives: The aim of this study was to investigate the influence of salivary contamination on bond strength to dentin during different application stages of 3 different adhesive systemsMaterials and Methods: Twenty-four caries-free human molars were sectioned horizontally with a diamond saw to expose 1 mm thick dentin disks. Totally 48 disks (two dentin disks from each tooth) were obtained and these disks were randomly divided into 3 groups according to adhesives used (Prime Bond NT, Clearfil SE Bond, Clearfil S3 Bond). Each adhesive group was further subdivided into 4 groups according to contamination methods as follows: no contamination which was the control group, contamination before adhesive application, contamination after adhesive application and contamination after polymerization of the adhesive. Transparent plastic cylindrical molds with an internal diameter of 0.7 mm and a height of 1 mm were used to place composite resin on dentin disks in order to test the microshear bond strength of the groups Three resin cylinders were attached on each dentin surface and 12 specimens were made for each group. Data were analyzed by one way ANOVA and Tukey's post hoc test.Results: Except when contamination occurred after the polymerization of two step self-etch adhesive, bond strength values of all groups showed statistically significant reduction compared with control groups (p<0.05).Conclusions: Within the limitations of this study, it can be concluded that, saliva contamination affects the bond strength to dentin of all adhesives used in this study and the type of adhesive and the stage of contamination can be effective on the bond strength of adhesive contaminated with saliva. Amaç: Bu çalışmanın amacı, 3 farklı adeziv sistemin farklı uygulama basamaklarında oluşan tükürük kontaminasyonunun, adeziv sistemlerin dentine bağlanma dayanımları üzerine etkisini incelemektir.Gereç ve Yöntem: Yirmi dört molar dişin kullanıldığı çalışmamızda, mikro kesit alma cihazıyla her bir dişten 2 adet olmak üzere toplam 48 adet 1 mm'lik horizontal dentin kesidi elde edilmiş ve bu kesitler, test edilen adeziv sistemin tipine göre (Prime Bond NT, Clearfil SE Bond, Clearfil S3 Bond) rastgele 3 gruba ayrılmıştır. Daha sonra her adeziv sistem için biri kontrol grubu olmak üzere tükürük kontaminasyonunun olduğu aşamaya göre (adeziv öncesi, adeziv sonrası ve polimerizasyon sonrası) 4 alt grup oluşturulmuştur. Her dentin diski üzerine 3 adet 0.7 mm çapında ve 1 mm yüksekliğinde kompozit rezin silindir yerleştirilmiştir (n=12) ve mikro makaslama test yöntemi uygulanmıştır. Veriler tek yön ANOVA ve Tukey çoklu karşılaştırma testi kullanılarak değerlendirilmiştir.Bulgular: İki basamaklı self-etch adezivin polimerizasyon sonrası grubu hariç diğer bütün grupların bağlanma dayanım değerlerinde kontrol grubuna göre düşüş saptanmıştır (p<0.05). Self-etch adezivlerde adeziv sonrası tükürük kontaminasyonu sonucu elde edilen değerler, adeziv öncesi tükürük kontaminasyonu sonucu elde edilen değerlere göre istatistiksel olarak daha yüksek bulunurken, etch and rinse adezivde bu 2 grup arasındaki farkın istatistiksel olarak anlamlı olmadığı görülmüştür (p<0.05).Sonuçlar: Tükürük kontaminasyonunun adeziv sistemlerin dentine bağlanma dayanımlarını etkilediği ve bu etkinin adeziv sistemin tipine ve kontaminasyonun olduğu basamağa göre değişiklik gösterdiği sonucuna varılabilir.